1998
DOI: 10.1128/jvi.72.7.5699-5706.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mouse Adenovirus Type 1 Early Region 1A in Acute and Persistent Infections in Mice

Abstract: Mouse adenovirus type 1 (MAV-1) early region 1A (E1A) viral mutants were used to determine the importance of this region in pathogenesis and establishment of a persistent infection in the natural host. Lethal dose analysis with adult male Swiss outbred mice revealed a significant reduction in virulence for all of the E1A mutants. During acute infections with 105 PFU of virus, an E1A null mutant,pmE109, was found in the same organs (brain, spleen, and spinal cord) and the same cell types (endothelial cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…Although the 50% lethal dose of pmE109 is higher than that of wt MAV-1 following i.p. infection of Swiss outbred mice (Smith et al, 1998), pmE109 was found in the same organs, including the brain, as wt MAV-1 following i.p. infection with 10 4 PFU (Smith et al, 1998).…”
Section: Detection Of Virus In the Brain Following Intranasal Infectionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the 50% lethal dose of pmE109 is higher than that of wt MAV-1 following i.p. infection of Swiss outbred mice (Smith et al, 1998), pmE109 was found in the same organs, including the brain, as wt MAV-1 following i.p. infection with 10 4 PFU (Smith et al, 1998).…”
Section: Detection Of Virus In the Brain Following Intranasal Infectionmentioning
confidence: 80%
“…Persistent infection is established following i.p. inoculation of NIH Swiss outbred mice, with virus shed in the urine and viral DNA detected in the brain, spleen, lymph nodes and kidneys for up to 55 weeks post-infection (Smith et al, 1998). Following i.p.…”
Section: Introductionmentioning
confidence: 99%
“…We were able to overcome this difficulty by using the mutant virus pmE109, which is null for E1A due to a site-directed mutation altering the initiator codon of the protein (39,40). pmE109 is less virulent than wt virus (39). In susceptible outbred mice the LD 50 of pmE109 is higher than that of wt virus (10 3.5 and Ͻ10 Ϫ1.0 PFU, respectively) ( Table 3) (39).…”
Section: Quantitation Of Virus Infection In Micementioning
confidence: 99%
“…177,178 Unlike HAdVs, which initially infect the respiratory epithelium, MAdV-1 replicates in the primary endothelial cells of various body systems and thus results in widespread systemic infection affecting the liver, spleen, kidneys, intestines, adrenals, heart, brain, and spinal cord. 179,180 The genome of MAdV-1 is ∼30.9 kbp and is similar to HAdV-5 in organization except that it does not encode virus-associated RNAs. 181,182 Vectors based on MAdV-1 were first described in the late 1990s.…”
Section: Murine Adenovirus-based Vectorsmentioning
confidence: 99%
“…184 However, the pathogenicity of E1A null mutants of MAdV-1 is significantly lower than wild-type virus, suggesting the requirement of E1A in the host but not in the cell culture. 179 The E3 region of MAdV-1 encodes for three proteins with a common N-terminal sequence but unique C-terminal sequences. 183 E3-deleted MAdV-1 vectors were constructed by mutagenesis to block expression of each one of the E3 proteins.…”
Section: Murine Adenovirus-based Vectorsmentioning
confidence: 99%